UI/UX DESIGN OF THE HOUSET WEBSITE AS A MARKETPLACE AND ROOM VISUALIZATION MEDIA - Ghaisani, Julia; Komariah, Siti Hajar; Aulia, Rahmiati (Telkom University, 2023)
PT. Houset Hunian Estetika is a startup engaged in interior design and furniture that makes it easy for the public to visualize the room and apply the room according to the desired interior design and sell furniture online. The way Houset makes it easy is by providing an interior design canvas in a 3D model so as to provide an experience for users in choosing the desired interior design and furniture. Houset also sells furniture that matches the interior design shown in 3D models. However, there is no media platform in the form of a website. With this phenomenon, the authors intend to build a platform for PT. Houset Hunian Estetika through the UI/UX design of the Houset website which is a means of marketplace and room visualization media. This research and design uses qualitative methods as data collection with a literature study approach, observation, interviews, questionnaires, matrix analysis and SWOT analysis. The design of this website is expected to make it easier for people to get furniture while helping to get a visual picture of the room in matching the interior design that is suitable for the room and helping its arrangement. Keywords: interior design, marketplace, PT. Houset Hunian Estetika, UI/UX, website design